Fabrication and simulation of surface plasmon resonance (SPR)-based tapered fiber sensor for E. coli detection. (2018) - Aminah, Nina Siti; Liani, Putri H.; Hendro; Hidayat, R.; Djamal, M.
Abstract: This paper presents fabrication and simulation using the finite difference time domain based on numerical tools of tapered optical fiber for a specific E. coli strain. To characterize the properties of these tapered optical fiber sensors, sugar solutions ranging from 0 to 50 in weight percent were utilized. The influence of the various parameters in the waveguide configurations is discussed in connection with optimum sensitivity and detection ranges of the sensors. The effect of the evanescent wave, refractive index, and reflection spectrum are studied with the presence of E. coli for deep-probe sensing. These findings can provide important and significant information to design better performance biosensor based on tapered optical fiber.